GABA strikes down again in epilepsy - Guazzi, Milena; Striano, Pasquale (Annals of Translational Medicine, 2019)
Disruption of GABA transmission has been associated with different epilepsy syndromes according to the role of GABA as the major inhibitory neurotransmitter in the central nervous system (CNS) (1).